THE SIGNIFICANCE OF PREVENTIVE MEASURES IN PREVENTING THE SPREAD OF TUBERCULOSIS AMONG THE POPULATION RESIDING IN THE REPUBLIC OF UZBEKISTAN - Nomozboyeva Maftuna Abduhamid kizi; Normurodova Hulkaroy Furkatjonovna; Abdurahmonova Dilnoza Komil qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In order to increase the importance of preventive measures in preventing the spread of tuberculosis among the population living in the Republic of Uzbekistan, the modern preventive measures and efforts aimed at preventing the modern epidemic in their spread are widely covered.